2007
DOI: 10.1111/j.1552-6569.2006.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Jugular Valve Insufficiency in Cerebral Venous Air Embolism

Abstract: This case report gives insight into the mechanism of cerebral venous air embolism. This is the firstcase describing jugular valve insufficiency as the missing link between peripheral air embolism and cerebral venous air entrapment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Retrograde rise of air bubbles against the venous blood flow is a mechanism described previously in literature, commonly following venous vascular intervention and there is speculation that its prevalence is underestimated [9] . It has also been suggested that jugular valve insufficiency can predispose to retrograde embolism in the neck, but this was not demonstrated on ultrasound of the neck in our case [11] .…”
Section: Discussioncontrasting
confidence: 75%
“…Retrograde rise of air bubbles against the venous blood flow is a mechanism described previously in literature, commonly following venous vascular intervention and there is speculation that its prevalence is underestimated [9] . It has also been suggested that jugular valve insufficiency can predispose to retrograde embolism in the neck, but this was not demonstrated on ultrasound of the neck in our case [11] .…”
Section: Discussioncontrasting
confidence: 75%
“…Among the published cases of cerebral venous air embolism related to central catheter use, air was most frequently demonstrated in the cortical veins [ 30–33 ] and the cavernous sinuses [ 33–36 ]. Moreover, air emboli involving the cavernous sinuses [ 37–40 ] and the jugular veins [ 39 , 40 ] have also been reported after peripheral bloodline manipulations. Normally the valves in the jugular vein ensure unidirectional blood flow towards the heart.…”
Section: Pathophysiology and Clinical Manifestationsmentioning
confidence: 99%
“…It was reported that air bubbles can cause cerebral venous embolism by retrograde flow in patients with central venous catheters depending on bubble volume, blood flow velocity, superior vena cava diameter and cardiac output 8 . Absence or insufficiency of valves in the jugular vein were presumed to be the cause for retrograde embolism 9 . External cardiac resuscitation was speculated to cause retrograde cerebral venous air embolism due to increased intrathoracic pressure 10 .…”
Section: Discussionmentioning
confidence: 99%